2002
DOI: 10.1021/ja016873q
|View full text |Cite
|
Sign up to set email alerts
|

How Does Internal Motion Influence the Relaxation of the Water Protons in LnIIIDOTA-like Complexes?

Abstract: Taking advantage of the Curie contribution to the relaxation of the protons in the Tb(III) complex, and the quadrupolar relaxation of the 17O and 2H nuclei on the Eu(III) complex, the effect of the internal motion of the water molecule bound to [Ln(DOTAM)(H2O)]3+ complexes was quantified. The determination of the quadrupolar coupling constant of the bound water oxygen chi(Omicron)(1 + eta(Omicron)2/3)1/2 = 5.2 +/- 0.5 MHz allows a new analysis of the 17O and 1H NMR data of the [Gd(DOTA)(H2O)]- complex with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
67
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 39 publications
11
67
0
Order By: Relevance
“…It appears that the bound water molecule retains some motional freedom regarding the orientation of the OH bond with respect to the metal ion (rotation around the Gd-O vector, variable tilting of the H-O-H plane). This finding was first published for the [Gd(EG-TA)(H 2 O)] -MD simulations [25] and soon found experimental support [34], with a ratio τ R (H)/τ R (O) = 0.65±0.3 for DOTA-like complexes.…”
Section: Rotational Correlation Timessupporting
confidence: 58%
“…It appears that the bound water molecule retains some motional freedom regarding the orientation of the OH bond with respect to the metal ion (rotation around the Gd-O vector, variable tilting of the H-O-H plane). This finding was first published for the [Gd(EG-TA)(H 2 O)] -MD simulations [25] and soon found experimental support [34], with a ratio τ R (H)/τ R (O) = 0.65±0.3 for DOTA-like complexes.…”
Section: Rotational Correlation Timessupporting
confidence: 58%
“…From simple geometrical models it can be shown that, even for the case of an extremely fast hypothetical internal rotation of the inner-sphere water molecule, the effective rotational correlation time for r GdH is only about 35 % shorter than that for r GdO . [44] The correlation time for the rotational motion of the whole complex, τ R (complex), can be obtained from the sum of all Gd-A vectors, where A are all binding atoms (N and O) of the macrocyclic or acyclic ligands. [20] The values of τ R (complex) for all complexes studied are close to those 66 [c] 58 [b] 58 [d] [a] Mean value for both protons of bound water molecules.…”
Section: Classical Molecular Dynamics Simulationsmentioning
confidence: 99%
“…[47][48][49] Quadrupole coupling constants of oxygen-17 have been determined for neat water, but only few, sometimes contradictory estimations are available for H 2 O molecules in the first coordination sphere of the cation. [44,[50][51][52][53] Model calculations on Gd-H 2 O clusters have been used to assess the dependence of 17 O quadrupole coupling parameters on the Gd-O distance and on the orientation of the water dipole vector of the first-sphere water molecules (tilt angle). [54] Only slight changes of χ and η with the Gd-O distance have been found.…”
Section: Quadrupolar Relaxation -Electric Field Gradientsmentioning
confidence: 99%
“…[10,12] Probably the hydrophobic moieties promote some kind of reversible association that causes an increase in the molecular correlation time, which in turn is responsible for yielding a r 1 value significantly larger than one would expect on the basis of M W increase alone. The t M value of Gd-L1 had been accurately determined by VT 17 O NMR T 2 measurements [13] as 65 ns at 298 K, that is, not too different from the parent Gd-DOTMA and still in the range of the optimal values for our purpose. Gd-L2 was not soluble enough for 17 O NMR measurements.…”
mentioning
confidence: 99%